2016
DOI: 10.4103/0300-1652.193856
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric predictors of hypertension: A cross-sectional study of women attending the postnatal clinic of Jos University Teaching Hospital

Abstract: Background:Hypertensive disease in pregnancy (HDP) accounts for high mother and child morbi-mortality and predict future cardiometabolic diseases. This study aimed to identify obstetric predictors of HDP needing preventive action to reduce its consequences; when women present to antenatal clinic (ANC).Materials and Methods:Cross-sectional descriptive this was an Interviewer-administered semi-structured questionnaire-based study of the anthropometric, and blood pressure measurementsin attendees at the postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For this variable, we found fourteen studies that had analysed the relationship between having a family history of HDP and the developing HDP [ 15 , 17 , 24 , 27 – 31 , 34 , 37 – 41 ]. All of these findings showed there was a positive association between family history of HDP and HDP in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this variable, we found fourteen studies that had analysed the relationship between having a family history of HDP and the developing HDP [ 15 , 17 , 24 , 27 – 31 , 34 , 37 – 41 ]. All of these findings showed there was a positive association between family history of HDP and HDP in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we found nine studies that reported on the association between a high BMI and HDP [ 17 , 23 , 24 , 29 – 31 , 36 , 42 , 45 ]. Out of those nine studies, seven studies revealed a significant association between high BMI and HDP [ 23 , 24 , 30 , 31 , 36 , 42 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations